Servicescapes Analysis of National Museum - Suwaryono, Ixora Lundia; Rosinta, Febrina; Soeling, Pantius Drahen (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
The existence of museums in big cities like Jakarta seemed to be neglected. The display inside a museum is often considered uninteresting, making visitors less appreciate the collection objects, thus receive no added value from their visit. Therefore, a research related to physical appearance of a museum is required. The physical appearance of a service organization, also called servicescapes, consists of ambient condition, layout and signage. A survey has been conducted to describe the importance of servicescape for National Museum, as well as the explanation about the subject. This research suggests some recommendations on the servicescapes in National Museum to improve visitors’ experience.